Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 609127 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Anser cygnoid (Linnaeus, 1758), Anser cygnoides (Linnaeus, 1758), Anser fabalis (Latham, 1787), Anser fabilis (Latham, 1787), Anser brachyrhynchus Baillon, 1834)", "BasisOfRecord is one of (Specimen, Human Observation, Observation, Machine Observation)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 609127 records from 274 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0337201-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences